2021
DOI: 10.3390/ma14092325
|View full text |Cite
|
Sign up to set email alerts
|

Controlled Nanostructuration of Cobalt Oxyhydroxide Electrode Material for Hybrid Supercapacitors

Abstract: Nanostructuration is one of the most promising strategies to develop performant electrode materials for energy storage devices, such as hybrid supercapacitors. In this work, we studied the influence of precipitation medium and the use of a series of 1-alkyl-3-methylimidazolium bromide ionic liquids for the nanostructuration of β(III) cobalt oxyhydroxides. Then, the effect of the nanostructuration and the impact of the different ionic liquids used during synthesis were investigated in terms of energy storage pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 59 publications
0
8
0
Order By: Relevance
“…Cobalt oxides and hydroxides are technologically important materials that have been adopted for a variety of applications including positive battery electrode materials (Li x CoO 2 and Na x CoO 2 ), thermoelectrics , (Na 2 Co 2 O 4 and Ca 3 Co 4 O 9 ), oxidation catalysts , (Co 3 O 4 ), superconductors and supercapacitors [CoOOH and Co­(OH) 2 ]. These materials crystallize in structurally related phases containing CoO 6 octahedra, often with close-packed O 2– anions, but are otherwise differentiated by the arrangement and stacking of these units and the distribution or ordering of Co and other cations relative to the oxygen sublattice.…”
Section: Introductionmentioning
confidence: 99%
“…Cobalt oxides and hydroxides are technologically important materials that have been adopted for a variety of applications including positive battery electrode materials (Li x CoO 2 and Na x CoO 2 ), thermoelectrics , (Na 2 Co 2 O 4 and Ca 3 Co 4 O 9 ), oxidation catalysts , (Co 3 O 4 ), superconductors and supercapacitors [CoOOH and Co­(OH) 2 ]. These materials crystallize in structurally related phases containing CoO 6 octahedra, often with close-packed O 2– anions, but are otherwise differentiated by the arrangement and stacking of these units and the distribution or ordering of Co and other cations relative to the oxygen sublattice.…”
Section: Introductionmentioning
confidence: 99%
“…Method 2: the b(III) cobalt oxyhydroxide phase is synthesized by forward precipitation at increasing pH (the pH value increases from 6 to 10 during the precipitation): 11 mL of 2 M NaOH solution is slowly added into the nitrate solution (3.18 g in 300 mL of distilled water) before the same oxidation, centrifugation and drying steps as seen for method 1. 29 The pure b(III) cobalt oxyhydroxides prepared by method 1 and by method 2 are denoted as b3-pH 14 and b3-pH b respectively.…”
Section: Preparation Of Cobalt Oxyhydroxide Precursorsmentioning
confidence: 99%
“…28 This cobalt phase displays indeed a very high electronic conductivity ($1 S cm −1 at room temperature) due to the presence of Co 4+ in the CoO 2 slabs. 29,30 The authors investigated the optimal molar ratio between the pseudocapacitive birnessite MnO 2 and the electronic conductive b3-CoOOH phase to reach the best capacity retention at high rates. It was found that a Mn : Co ratio of 3 : 1 exhibits the greatest synergetic effect between both phases leading to a composite with better rate performance than simple manganese oxide or MnO 2 mixed with carbon black.…”
Section: Introductionmentioning
confidence: 99%
“…Just after this step, the solution is titrated by sodium thiosulfate solution to obtain V eq , which represents the volume of added sodium thiosulfate when the yellow solution turns to transparent. The principle of iodometric titration is explained in ref 19.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%